Discourse Content Analysis of Illocutionary Speech Act in Pragmatic Text - Andri Purwanto; Miftahulkhairah Anwar (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This research is motivated by the existence of illocutionary speech acts in the dialogue of Hazel's character in the film The Fault in Our Stars by John Green. This research aims to describe the types of illocutionary speech acts and the functions of illocutionary speech acts in Hazel's dialogue in John Green's The Fault in Our Stars. The methodology used in this research was a descriptive qualitative method with a library technique data search method. The data source for this research was the film The Fault in Our Stars which was released in 2014. All illocutionary utterances contained in Hazel's dialogues in the film The Fault in Our Stars were the object of this research. Data collection was done by writing and note method. The results of this research indicate that there are five types of illocutionary speech acts found in Dilan's dialogue in the film The Fault in Our Stars, namely assertive illocutionary speech acts, directive speech acts, commissive speech acts, expressive speech acts and declarative speech acts.